FUTURE TECHNOLOGY TEACHERS’ PROFESSIONAL TRAINING IN TERMS OF UKRAINE’S INTEGRATION INTO THE EUROPEAN EDUCATIONAL SPACE - Kurok, Vira; Voitelieva, Galyna (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2017)
The peculiarities and tendencies of educational space development in countries of Europe were characterized in the process of studying the European experience of future specialists’ professional training. The current state of future Technology teachers’ professional training in Ukraine was analyzed. The congruence of the Ukrainian educational system to the requirements of the European educational space was established. The ways of improving the professional staff training for the purpose of European integration are defined.